2013
DOI: 10.1038/npp.2013.144
|View full text |Cite
|
Sign up to set email alerts
|

Error Correction in Latent Inhibition and its Disruption by Opioid Receptor Blockade with Naloxone

Abstract: Latent inhibition refers to the retardation in the development of conditioned responding when a pre-exposed stimulus is used to signal an unconditioned stimulus. This effect is described by error-correction models as an attentional deficit and is commonly used as an animal model of schizophrenia. A series of experiments studied the role of error-correction mechanism in latent inhibition and its interaction with the endogenous opioid system. Systemic administration of the competitive opioid receptor antagonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Many compelling studies have shown that opioid receptor is responsible for analgesic effects and is a target for many analgesic drugs. In the present study, we used morphine, a classical analgesic drug which is an agonist of opioid receptor [ 24 ] and naloxone, an antagonist of opioid receptor [ 21 ], to study if the analgesic effect of EE is dependent on opioid receptor. As shown in Figure 3 , compared with CG, treatment with EE slightly increased response latency at every time point (30, 60, 90, and 120 min) in mice, but intriguingly, these mild analgesic effects failed to be alleviated by naloxone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many compelling studies have shown that opioid receptor is responsible for analgesic effects and is a target for many analgesic drugs. In the present study, we used morphine, a classical analgesic drug which is an agonist of opioid receptor [ 24 ] and naloxone, an antagonist of opioid receptor [ 21 ], to study if the analgesic effect of EE is dependent on opioid receptor. As shown in Figure 3 , compared with CG, treatment with EE slightly increased response latency at every time point (30, 60, 90, and 120 min) in mice, but intriguingly, these mild analgesic effects failed to be alleviated by naloxone.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our observation is in tune with the recent studies conducted by Chang et al [ 30 ] and Li et al [ 31 ], who have shown that EE can improve peripheral nerve regeneration and exhibits analgesic activity. Simultaneously, we used naloxone, an antagonist of opioid receptor [ 21 ] which plays a pivotal role in central nociceptive system, to block opioid receptor, and found that naloxone exhibited no effects on analgesic effects of EE in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work will test this hypothesis, the effects of naloxone on extinction of second-order and sensory preconditioned fear, and finally, the neural substrates of these effects in the BLA. Specifically, it will examine whether naloxone impairs extinction of second-order and sensory preconditioned fear in the same way as it has been shown to impair the extinction of first-order fear and other forms of learning produced by CS alone exposure (e.g., latent inhibition; Leung et al, 2013 ); and whether naloxone achieves its effects on second-order conditioning and sensory preconditioning via its effects in the BLA.…”
Section: Discussionmentioning
confidence: 99%
“…Latent inhibition is most often assessed using fear conditioning procedures. Opioid receptor antagonists, such as naloxone (2.5 mg/kg), blocked latent inhibition of fear conditioning in male Wistar rats (Leung et al, 2013). Interestingly, although nor-BNI prevented the renewal of fear in response to a conditioned stimulus, nor-BNI failed to affect context-dependent latent inhibition of fear (Cole et al, 2011).…”
Section: Opioid Ligands and Cognitive Function – Preclinical Evidencementioning
confidence: 99%